1990
DOI: 10.1093/mutage/5.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic activity of some saponins isolated from Calendula officinalis L., C. arvensis L. and Hedera helix L.

Abstract: Thirteen saponins were isolated and identified from Calendula officinalis, C. arvensis and Hedera helix. Mutagenic and antimutagenic activities of these products were investigated using a modified liquid incubation technique of the Salmonella/microsomal assay. The Salmonella tester strain TA98 +/- S9 mix was used. Screening of the antimutagenic activity was performed with a known promutagen: benzo-[a]pyrene (BaP) and a mutagenic urine concentrate from a smoker (SU). Antimutagenic activities were also compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…Pot marigold possesses the anti-inflammatory, antibacterial, wound healing, spasmolytic, hypotensive and sedative properties, increases the metabolic function of the liver. A wide therapeutic activity of calendula is explained by the presence of a considerable number of carotenoids, flavonoids, salicylic acid, vitamins and other compounds [8][9][10][11].…”
Section: This Article Presents the Results Of The Study Of The Procesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pot marigold possesses the anti-inflammatory, antibacterial, wound healing, spasmolytic, hypotensive and sedative properties, increases the metabolic function of the liver. A wide therapeutic activity of calendula is explained by the presence of a considerable number of carotenoids, flavonoids, salicylic acid, vitamins and other compounds [8][9][10][11].…”
Section: This Article Presents the Results Of The Study Of The Procesmentioning
confidence: 99%
“…Pot marigold possesses the anti-inflammatory, antibacterial, wound healing, spasmolytic, hypotensive and sedative properties, increases the metabolic function of the liver. A wide therapeutic activity of calendula is explained by the presence of a considerable number of carotenoids, flavonoids, salicylic acid, vitamins and other compounds [8][9][10][11].At chemical and pharmaceutical enterprises Calendula tincture is obtained by simple maceration or percolation with 70° ethanol [1,3].These methods of tincture production do not meet modern requirements since the time required to obtain the finished product is long enough, and the plant raw material is exhausted only by 70% [2,3,5,7].Pressure enhanced solvent extraction takes the conventional solvent based extraction technology to a new level. This extraction technology effectively combines the use of solvents and elevated pressures to provide superior yields of high quality extracts from naturally occurring materials [4].…”
mentioning
confidence: 99%
“…It also has polyphenolic compounds including flavonoids and tannins in its aerial parts [6] as well as thirteen saponins [7]. Its leaves contain flavonoids and glycosides like Kaempferol 3-mono-glycosides and Quercetin 3-mono or diglycosides [8].…”
Section: Introductionmentioning
confidence: 99%
“…1) distributed in Hedera or Nigella species displays many biological activities such as hemolytic, antispasmodic (Trute et al, 1997), antiinflammatory (Choi et al, 2002a(Choi et al, , 2002bKim et al, 2002), antileishmanial (Delmas et al, 2000;Ridoux et al, 2001), molluscicidal and cytotoxic (Park et al, 2001), partially due to their interaction with the cell membrane (Chwalek et al, 2006). α-Hederin is increasingly investigated for its promising antitumor potential since it revealed cytotoxicity against various cancer cell lines (Quetin-Leclercq et al, 1992;Danloy et al, 1994;Rooney and Ryan, 2005a;Tian et al, 2006) and in vivo tumors (Kumara and Huat, 2001) with antimutagenic activity (Elias et al, 1990;Amara-Mokrane et al, 1996;Lee et al, 2000). It has been suggested that α-hederin exerts its cytotoxic activity by promoting apoptosis and/or membrane alterations, although the molecular and cellular mechanisms are far from being fully elucidated (Swamy and Huat, 2003;Rooney and Ryan, 2005b).…”
Section: Introductionmentioning
confidence: 99%